Long Non-Coding RNA Cancer Susceptibility Candidate 9 Regulates the Malignant Biological Behavior of Nasopharyngeal Carcinoma Cells by Targeting miR-497-5p/Wnt3a/β-catenin Signaling Pathway - Lei, Yue; Luo, Wenlong; Gong, Qiuyue; Luo, Lan; Jing, Wuyang (Frontiers in Oncology, 2022)
Nasopharyngeal carcinoma (NPC) is a major kind of head and neck epithelial carcinoma. Increasing evidences reveal that long noncoding RNAs are considered as vital regulators in tumorigenesis and progression. Although previous studies have found that cancer susceptibility candidate 9 (CASC9) highly expresses in NPC, the underlying mechanisms need to be further studied. In this study, we found that CASC9 was overexpressed and associated with worse prognosis in NPC. CASC9 knockdown significantly inhibited the cell proliferation, migration and invasion in vitro and enhanced the sensitivity of tumor cells to cisplatin and paclitaxel. Mechanism research confirmed CASC9 regulated the malignant biological behavior of nasopharyngeal carcinoma cells by targeting miR-497-5p/Wnt3a/β-catenin signaling pathway. The present study might provide a novel mechanism for tumorigenesis and progression of NPC and contribute to the development of an effective molecular target therapy.